Topographical anatomy of the mandibular foramen in the dromedary camels (Camelus dromedarius): an extraoral approach for the inferior alveolar nerve blocks - Al Mohamad, Zakriya; Hamed, Mohamed; Abdellatif, Ahmed; Eldoumani, Haitham; Elshafaey, Elsayed; Abouelnasr, Khaled (Frontiers in Veterinary Science, 2023)
Understanding the clinical anatomy of the head is essential for conducting performing proper inferior alveolar nerve (IAN) block anesthesia to facilitate invasive dental procedures in camels.However, osteometric data related to the IAN in camels are lacking. This study was carried out to accurately locate the mandibular foramen (MF) and the course of the IAN in the camel head and to Formatted: Font: (Default) +Headings CS (Times New Roman), 14 pt, Font color: Red, Complex Script Font: +Headings CS (Times New Roman), 14 pt, Pattern: Clear